Method and Role for Cultivating Emotional Intelligence in Music Education - Jia, Cong; Ayob, Adenan (Journal of Theory and Practice in Education and Innovation, 2025)
This paper aim to study cultivating Emotional Intelligence (EI) in music education, emphasizing its significance in enhancing both individual and collaborative musical performance. Emotional Intelligence, encompassing self-awareness, self-regulation, empathy, and social skills, is a crucial factor in fostering emotional expression and teamwork in musical contexts. Despite its recognized importance, limited frameworks exist for effectively integrating EI into music education. This study aims to identify and evaluate practical teaching approaches, including mindfulness exercises, reflective practices, and collaborative learning activities, that support the development of EI among music students. Utilizing a mixed-methods approach, the research combines quantitative analysis of performance outcomes with thematic analysis of reflective journals to assess the effectiveness of these strategies. Findings indicate that EI-focused interventions improve emotional communication, enhance collaboration in ensembles, and empower students to navigate the emotional complexities of musical expression. The paper concludes with actionable recommendations for music educators to embed EI training into curricula, fostering a generation of emotionally intelligent and expressive musicians.